NNMT contributes to high metastasis of triple negative breast cancer by enhancing PP2A/MEK/ERK/c-Jun/ABCA1 pathway mediated membrane fluidity. (28th October 2022) - Wang, Yanzhong; Zhou, Xi; Lei, Yinjiao; Chu, Yadong; Yu, Xingtong; Tong, Qingchao; Zhu, Tao; Yu, Haitao; Fang, Sining; Li, Guoli; Wang, Linbo; Wang, Gavin Y.; et al.
Abstract: Elucidating the mechanism for high metastasis capacity of triple negative breast cancers (TNBC) is crucial to improve treatment outcomes of TNBC. We have recently reported that nicotinamide N-methyltransferase (NNMT) is overexpressed in breast cancer, especially in TNBC, and predicts poor survival of patients undergoing chemotherapy. Here, we aimed to determine the function and mechanism of NNMT on metastasis of TNBC. Additionally, analysis of public datasets indicated that NNMT is involved in cholesterol metabolism. In vitro, NNMT overexpression promoted migration and invasion of TNBCs by reducing cholesterol levels in the cytoplasm and cell membrane. Mechanistically, NNMT activated MEK/ERK/c-Jun/ABCA1 pathway by repressing protein phosphatase 2A (PP2A) activity leading to cholesterol efflux and membrane fluidity enhancement, thereby promoting the epithelial-mesenchymal transition (EMT) of TNBCs. In vivo, the metastasis capacity of TNBCs was weakened by targeting NNMT. Collectively, our findings suggest a new molecular mechanism involving NNMT in metastasis and poor survival of TNBC mediated by PP2A and affecting cholesterol metabolism. Highlights: NNMT is overexpressed in TNBC and predicts high metastasis and poor survival. NNMT promotes migration and invasion of TNBCs by enhancing membrane fluidity and EMT. NNMT promotes membrane fluidity and EMT of TNBCs by reducing cell cholesterol. NNMT activates PP2A/MEK/ERK/c-Jun/ABCA1 pathway to enhance cholesterol efflux. The metastasis capacity of TNBCs was weakened by targeting NNMT in vivo .